Are we prepared? The development of performance indicators for public health emergency preparedness using a modified Delphi approach. - Yasmin Khan; Adalsteinn D Brown; Anna R Gagliardi; Tracey O'Sullivan; Sara Lacarte; Bonnie Henry; Brian Schwartz (PLoS ONE)
Background Disasters and emergencies from infectious diseases, extreme weather and anthropogenic events are increasingly common. While risks vary for different communities, disaster and emergency preparedness is recognized as essential for all nation-states. Evidence to inform measurement of preparedness is lacking. The objective of this study was to identify and define a set of public health emergency preparedness (PHEP) indicators to advance performance measurement for local/regional public health agencies. Methods A three-round modified Delphi technique was employed to develop indicators for PHEP. The study was conducted in Canada with a national panel of 33 experts and completed in 2018. A list of indicators was derived from the literature. Indicators were rated by importance and actionability until achieving consensus. Results The scoping review resulted in 62 indicators being included for rating by the panel. Panel feedback provided refinements to indicators and suggestions for new indicators. In total, 76 indicators were proposed for rating across all three rounds; of these, 67 were considered to be important and actionable PHEP indicators. Conclusions This study developed an indicator set of 67 PHEP indicators, aligned with a PHEP framework for resilience. The 67 indicators represent important and actionable dimensions of PHEP practice in Canada that can be used by local/regional public health agencies and validated in other jurisdictions to assess readiness and measure improvement in their critical role of protecting community health.